Procalcitonin for detecting community-acquired bacterial pneumonia - Devi Gusmaiyanto; Finny Fitry Yani; Efrida Efrida; Rizanda Machmud (Paediatrica Indonesiana, 2015)
Background Pneumonia is a major cause of morbidity andmortality in children under five years of age. Pneumonia can be ofbacterial or viral origin. It is difficult to distinguish between thesetwo agents based on clinical manifestations, as well as radiologicaland laboratory examinations. Furthermore, bacterial cultures taketime to incubate and positive results may only be found in 10-30%of bacterial pneumonia cases. Procalcitonin has been used as amarker to distinguish etiologies, as bacterial infections tend toincrease serum procalcitonin levels.Objective To determine the sensitivity, specificity, positivepredictive value and negative predictive value of procalcitoninin community-acquired bacterial pneumonia.Method This cross-sectional study was conducted in thePediatric Health Department of Dr. M. Djamil Hospital, Padang.Subjects were selected by consecutive sampling. Procalcitoninmeasurements and PCR screening were performed on bloodspecimens from 32 pneumonia patients and compared.Results Of the 32 subjects, most were boys (56.25%), under 5years of age (99%), and had poor nutritional status (68.75%).Using a cut-off point of 0.25 ng/mL, procalcitonin level hada sensitivity of 92%, specificity 50%, positive predictive value 88%, and negative predictive value 60% for diagnosing bacterial pneumonia. Using a cut-off point of 0.5 ng/mL, procalcitonin level had a specificity of 46%, specificity 83%, positive predictive value 91%, and negative predictive value 25%.Conclusion A cut-off point of 0.25 ng/mL of procalcitonin level may be more useful to screen for bacterial pneumonia than a cutoff point of 0.5 ng / mL. However, if the 0.25 ng/mL cut-off point is used, careful monitoring will be required for negative results, as up to 40% may actually have bacterial pneumonia. [PaediatrIndones. 2015;55:65-9.].